As crenças de formandos de português e de espanhol acerca da variação linguística: um estudo na perspectiva da complexidade - Yana Liss Soares Gomes (2014)
This work is the fruit of a field research with the main objective to analyze the beliefs of the students/learners major in Spanish and Portuguese Languages of the State University of Piaui (UESPI) about linguistic variation. Starting from the paradigm ofthe complexity, we resort to the Chaos/Complexity Theory in order to comprehend the dynamics and the complexity of the beliefs and their relation to the universe of the formation of teachers of languages and to the teaching and learning processes.The sociolinguistic assumptions were resumed in order to discuss some related topics between the teaching of Maternal Language (ML) and the teaching of Foreign Language (FL), that is: tongue/language, linguistic myths and linguistic diversity.Through the cross- checking of some factors identified on the aspect of beliefs around the statute of languages, its heterogeneous character, and its teaching, we identify that the diverse beliefs of the students of Portuguese and Spanish are related in a systematic form, such that the different elements of this system, apparently not inorder, are structured in networks organized in a central and/or peripheral form. The central beliefs referent to the tongue/language and to the linguistic myths seem to be more resistant to the interferences of the diverse agents; while the peripheral beliefsrelated to the phenomenon of the linguistic variation are more easily (re)constructed, that is, modified, especially in the universe of the formation of teachers. Through the cross- checking of the data, we identify, in the midst of the diversity of the beliefs,countless similarities related to beliefs in tongue/language as the instrument of communication, disagreement of some linguistic myths and the standards related to disagreement of the discourse that The place where Portuguese is better spoken inBrazil is in Maranhão and the recognition of the linguistic diversity as a phenomenon inherent to the languages appeared in the course of the fixation and/or the (re)construction of the beliefs of the students of the two courses about linguistic variation. However, even if the initial conditions are similar, we cannot affirm that the beliefs will be equal in function of the dynamics and the complexity of theagents/factors that influence the system of beliefs of every student, above all, in function of the action of the diverse external agents, among which the contextual factors, sociocultural factors and the many educational experiences lived by those students. The results that we found suggest that due to the paradoxical character ofthe beliefs, there will be countless in implications of this for the formation of teachers in languages, as well as for the teaching/learning processes of the ML and FL, the conscientization and the raising of the awareness of the students in relation to the linguistic variation.